THE EFFECT OF USING YOUTUBE ON STUDENTS’ VOCABULARY MASTERY GRADE NINE AT SMP NEGERI 4 PEMATANG SIANTAR - Rahel Manik; David Berthony Manalu; Leonita Efipanias Manihuruk (CV SWA Anugrah, 2023)
The Effect of Using YouTube On Students’ Vocabulary Mastery Grade Nine at SMP Negeri 4 Pematang Siantar in 2023/2024 Academic Year. The aim of this research is to find out the effect of using YouTube on Students' Vocabulary Mastery Grade Nine at SMP Negeri 4 Pematangsiantar. This research used quantitative research method with quasi-experimental design. The population were grade nine students at SMP Negeri 4 Pematangsiantar. The researcher used two classes were 31 students both of class as sample, where one class was as the experimental class and the other one was the control class. Class IX-9 was the experimental class and class IX-10 was the control class. The instrument for collecting the data was 20 multiple choice tests. The data were analyzed by applying the T-test. It is found that the T-test 1,8 is higher than the T-table 1,671 at the level of significance 5% for two tailed test, so the null hypothesis (HO) is rejected and the alternative hypothesis (Ha) is accepted. This means that using YouTube develops students' vocabulary mastery.